Infrared image segmentation based on Otsu and genetic algorithm - Shunyong Zhou; Pingxian Yang (2011 International Conference on Multimedia Technology, 2011)
The infrared image is formed by the thermal infrared rays of the targets and environment. As the targets radiate more heat, we can see they have larger grey-scale, locating in the top-end of histogram. According to this characteristic of infrared images, a new method for infrared image segmentation based on Otsu and genetic algorithm is proposed in this paper. First, covert the infrared image to grayscale image; Second, detect the image edge, and get the best threshold for image segmentation by Otsu and GA (Otsu-GA); Finally, Segment the image by the threshold, and contrast the results of two peaks and iteration. Experimental results show that the method effectively improved the quality of image segmentation.